2008
DOI: 10.2135/cropsci2007.07.0405
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crumb Rubber Topdressing on Hybrid Kentucky Bluegrass and Bermudagrass Athletic Fields in the Transition Zone

Abstract: New turfgrass varieties and management practices have introduced new options for transition zone athletic field managers. Our objectives were to determine the wear tolerance of four turfgrasses in the transition zone with and without crumb rubber under simulated athletic field conditions, and to determine if improved cool and warm‐season turfgrass species can be used for transition zone athletic fields. Field trials evaluated the use of four turfgrass species with and without crumb rubber topdressing in Knoxvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
4
32
1
Order By: Relevance
“…These results are inconsistent with percent green coverage data in Tennessee under low (two passes weekly) traffic intensity (12,21), as well as under percent vegetative coverage in Arkansas across low and high (six passes weekly) traffic intensities (12). However, these results are consistent with green and vegetative coverage results under high traffic intensity and when vegetative coverage was evaluated under low traffic intensity in Tennessee (12). Tifway, Riviera and Yukon bermudagrass performed similarly in our trial in the fall.…”
Section: Bermudagrass Traffic Tolerancecontrasting
confidence: 85%
See 1 more Smart Citation
“…These results are inconsistent with percent green coverage data in Tennessee under low (two passes weekly) traffic intensity (12,21), as well as under percent vegetative coverage in Arkansas across low and high (six passes weekly) traffic intensities (12). However, these results are consistent with green and vegetative coverage results under high traffic intensity and when vegetative coverage was evaluated under low traffic intensity in Tennessee (12). Tifway, Riviera and Yukon bermudagrass performed similarly in our trial in the fall.…”
Section: Bermudagrass Traffic Tolerancecontrasting
confidence: 85%
“…× C. transvaalensis Burtt-Davy] was reported to have similar wear (25) and traffic (5,24) tolerance to 'Tifsport' hybrid bermudagrass. Riviera and Tifway were shown to have similar traffic tolerance (8,24) and improved traffic tolerance compared to Quickstand (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Goddard et al (2008) also reported lower surface hardness values on several bermudagrass cultivars retaining greater green cover after receiving crumb rubber topdressing before simulated traffic. Goddard et al (2008) also reported lower surface hardness values on several bermudagrass cultivars retaining greater green cover after receiving crumb rubber topdressing before simulated traffic.…”
Section: Surface Hardness and Rotational Resistancementioning
confidence: 87%
“…Mean turfgrass ground cover was greatest (≥ 80%) in the treatments that received crumb rubber alone or a 2.4‐cm layer of USGA sand then a 2.4‐cm layer of crumb rubber, followed by treatments that received a 4.8‐cm layer of USGA sand, then treatments that received CPG, NPSD, and USGAF sand, and finally the non‐topdressed control, which produced the lowest turfgrass cover values. Prior research has also determined that crumb rubber topdressing at a 2.0‐cm depth can provide increased Kentucky bluegrass and bermudagrass cover in the transition zone (12), and Kentucky bluegrass‐perennial ryegrass cover in a cool‐season climate after traffic simulation (24). Similar results were reported for bermudagrass ( Cynodon dactylon ) quality, stand density, and rooting as a result of a 6.0‐mm sand topdressing layer (18).…”
Section: Effects Of Topdressing Materials On Turfgrass Cover and Shearmentioning
confidence: 99%